School-based mental health promotion in children and adolescents with StresSOS using online or face-to-face interventions: study protocol for a randomized controlled trial within the ProHEAD consortium - Eschenbeck, Heike; Bauer, Stephanie; Kaess, Michael; Salize, Hans Joachim; Moessner, Markus (Trials, 2019)
Schools are an ideal setting in which to promote health. However, empirical data on the effectiveness of school-based mental health promotion programs are rare, and research on universal Internet-based prevention in schools is almost non-existent. Following the life skills approach, stress management training is an important component of health promotion. Mental health literacy is also associated with mental health status, and it facilitates formal help-seeking by children and adolescents (C&A). The main objectives of this study are (1) the development and evaluation of an Internet-based version of a universal school-based health promotion program called StresSOS and (2) demonstrating non-inferiority of the online setting compared to the face-to-face setting. StresSOS aims to improve stress management and mental health literacy in C&A.